On some of the Contributions Made by Professor Peter Kostić to the Development of Psychology - Davidović, Jelena; Pavićević, Miljana (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The paper aims to highlight the contribution made by professor Petar Kostić to the development of psychology. By dealing both successively and simultaneously with his two professions, military studies and psychology, the professor made the boundaries between them bilaterally permeable. As a result, both of these areas have become richer; in regard to military topics, psychology expanded to them as well.The paper first outlines the professional career and research path of professor Kostić, and then briefly outlines some of his papers in the field of personality psychology. When the aforementionedpapers were written, professor Kostić dealt with the field of personality psychology in the context of current topics: the wounded, veterans, Internet addiction, as well as eternal topics: lying, happiness, fear of death.Many awards he received testify to the importance and contribution of the professor’s research into both military studies and psychology. The recognition of students of the Faculty of Philosophy in Priština with temporary head office in Kosovska Mitrovica bears testament to the quality of his teaching methodology.
Keywords: professor Petar Kostić; contribution; psychology; awards